Grow a flower:dk - Clyne, Margaret (Pearson Education Harlow, 2010)
"Grow a Flower" is an engaging children's book that introduces young readers to the process of planting and nurturing flowers. Through simple, clear text and vibrant illustrations, it explains the steps involved in growing a flower, from choosing seeds and preparing the soil to watering and caring for the plant as it grows.